PENGARUH INTELLECTUAL CAPITAL DAN LEVERAGE TERHADAP RETURN ON ASSET PADA PERUSAHAAN HIGH TECHNOLOGY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ziah Ayu Nabila (Accounting Journal of Ibrahimy (AJI), 2024)
Companies engaged in the high technology sector often face intense competition in their business environment, where financial performance plays a central role in determining the continuity and achievement of the company. This encourages every company to make strategic changes in their business operations in order to improve the company's financial performance. This study aims to examine the effect of intellectual capital and leverage on return on assets in high technology companies listed on the Indonesia Stock Exchange in 2020-2022. Using a quantitative descriptive analysis research approach with a sample of 37 companies resulting in 111 observations. The sampling technique used purposive sampling technique. The independent variables used are intellectual capital and leverage, while the dependent variable is ROA. The data analysis method uses panel data regression analysis. Based on the results of the study, intellectual capital has a positive effect on return on assets, while leverage has a negative effect on return on assets in high technology companies listed on the IDX. This research is expected to provide benefits for academics, companies, and investors. Academics can expand their understanding of the effect of intellectual capital and leverage on return on assets of high technology companies on the IDX. Companies and investors can use the results for performance evaluation and investment decision making.